1994
DOI: 10.1183/09031936.94.07081397
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline does not protect against hyperoxic lung injury in rats

Abstract: P Pe en nt to ox xi if fy yl ll li in ne e d do oe es s n no ot t p pr ro ot te ec ct t a ag ga ai in ns st th hy yp pe er ro ox xi ic c l lu un ng g i in nj ju ur ry y i in n r ra at ts s The drug pentoxifylline has been shown to have a protective effect in other models of lung injury. We sought to determine whether pentoxifylline protects against hyperoxic lung injury in rats by decreasing the accumulation of neutrophils within the lung. A total of 84 rats were studied. Twenty four rats were randomized into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
6
1
1
Order By: Relevance
“…Support for this hypothesis is the fact that in some circumstances, PTX may enhance neutrophil migration and accumulation in lung tissues at concentrations sufficient to induce an anti-inflammatory effect. 38,39 The concentration of PTX required for inhibition of cytokine production in live horses is unknown, but PTX concentrations lower than those obtained in the study reported here have inhibited the production of proinflammatory cytokines in several in vitro equine models. 10,23 Based on results of the study reported here, it can be concluded that the administration of PTX improves respiratory function of RAO-affected horses.…”
Section: Discussionmentioning
confidence: 69%
“…Support for this hypothesis is the fact that in some circumstances, PTX may enhance neutrophil migration and accumulation in lung tissues at concentrations sufficient to induce an anti-inflammatory effect. 38,39 The concentration of PTX required for inhibition of cytokine production in live horses is unknown, but PTX concentrations lower than those obtained in the study reported here have inhibited the production of proinflammatory cytokines in several in vitro equine models. 10,23 Based on results of the study reported here, it can be concluded that the administration of PTX improves respiratory function of RAO-affected horses.…”
Section: Discussionmentioning
confidence: 69%
“…The initial event appears to be damage to the capillary endothelium, followed by platelet adhesion and PMN accumulation in the capillary vessels and interstitium (13,82). Eventually, alveolar epithelial injury occurs, with an increase in microvascular permeability measured as wet-to-dry (W/D) ratios and migration of neutrophils into the air spaces, as evidenced by increase in total numbers in BAL fluid (18,20,102,148). The pulmonary architecture is preserved during this early phase (82).…”
Section: Models That Target Primarily the Alveolar Epitheliummentioning
confidence: 95%
“…In rats and mice, exposure to 100% O 2 for 40 -50 h results in ALI, and longer exposure (60 -70 h) results in death (13,18,63,148). Survival after exposure to O 2 is age dependent, as neonates are more tolerant to hyperoxia and survive for up to 7 days (67).…”
Section: Models That Target Primarily the Alveolar Epitheliummentioning
confidence: 99%
“…This issue of the Journal contains an article by NAURECKAS et al [19] reporting that POF does not protect against hyperoxic lung injury in rats. This paper is of great interest, because it demonstrates that the protective effect of POF depends on the cause of lung injury.…”
mentioning
confidence: 99%